Multiple perspectives on quality of life for residents with dementia in long term care facilities: protocol for a comprehensive Australian study. (22nd April 2015) - Beattie, Elizabeth; O'Reilly, Maria; Moyle, Wendy; Chenoweth, Lynn; Fetherstonhaugh, Deirdre; Horner, Barbara; Robinson, Andrew; Fielding, Elaine
ABSTRACT: Background: Dementia is a chronic illness without cure or effective treatment, which results in declining mental and physical function and assistance from others to manage activities of daily living. Many people with dementia live in long term care facilities, yet research into their quality of life (QoL) was rare until the last decade. Previous studies failed to incorporate important variables related to the facility and care provision or to look closely at the daily lives of residents. This paper presents a protocol for a comprehensive, multi-perspective assessment of QoL of residents with dementia living in long term care in Australia. A secondary aim is investigating the effectiveness of self-report instruments for measuring QoL. Methods: The study utilizes a descriptive, mixed methods design to examine how facility, care staff, and resident factors impact QoL. Over 500 residents with dementia from a stratified, random sample of 53 facilities are being recruited. A sub-sample of 12 residents is also taking part in qualitative interviews and observations. Conclusions: This national study will provide a broad understanding of factors underlying QoL for residents with dementia in long term care. The present study uses a similar methodology to the US-based Collaborative Studies of Long Term Care (CS-LTC) Dementia Care Study, applying it to the Australian setting.